2015
DOI: 10.1088/1748-9326/10/4/044017
|View full text |Cite
|
Sign up to set email alerts
|

Presence of nitrous oxide hotspots in the coastal upwelling area off central Chile: an analysis of temporal variability based on ten years of a biogeochemical time series

Abstract: Seasonal and inter-annual variabilities of biogeochemical variables, including nitrous oxide (N 2 O), an important climate active gas, were analyzed during monthly observations between 2002 and 2012 at an ocean Time-Series station in the coastal upwelling area off central Chile (36°30.8′; 73°15′).Oxygen, N 2 O, nutrients and chlorophyll-a (Chl-a) showed clear seasonal variability associated with upwelling favorable winds (spring-summer) and also inter-annual variability, which in the case of N 2 O was clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 55 publications
6
52
0
2
Order By: Relevance
“…We have previously highlighted clinical case reports 13 , as well as several animal studies 14,15,16 , which indicated the role of N 2 O exposure in reducing epileptiform seizure activity 17 , while withdrawal from the drug has been shown to induce seizure-like activity 14,15,16 . Our novel environmental N 2 O-mediated hypothesis of neurodevelopmental impairment is supported by recent evidence indicating N 2 O hotspots in central Chile, given the following statement from the work: "…in our study area (off central Chile), they have ΔN 2 O three times higher than the average monthly ΔN 2 O… the increased N 2 O production seemed to be caused by the addition of anthropogenic NO 3 -associated with strong river runoff and a subsequent reduction to N 2 O (i.e., partial denitrification) 18 . " However, the aforementioned analyses by Cakmak et al…”
supporting
confidence: 88%
See 1 more Smart Citation
“…We have previously highlighted clinical case reports 13 , as well as several animal studies 14,15,16 , which indicated the role of N 2 O exposure in reducing epileptiform seizure activity 17 , while withdrawal from the drug has been shown to induce seizure-like activity 14,15,16 . Our novel environmental N 2 O-mediated hypothesis of neurodevelopmental impairment is supported by recent evidence indicating N 2 O hotspots in central Chile, given the following statement from the work: "…in our study area (off central Chile), they have ΔN 2 O three times higher than the average monthly ΔN 2 O… the increased N 2 O production seemed to be caused by the addition of anthropogenic NO 3 -associated with strong river runoff and a subsequent reduction to N 2 O (i.e., partial denitrification) 18 . " However, the aforementioned analyses by Cakmak et al…”
supporting
confidence: 88%
“…Consistent with the future goals identified by Chilean health and government officials 5 , we attempt to qualify the prior work by these research groups by performing regression analyses using a state-based total of farm use of anthropogenic nitrogen fertilizer, which is thought to be the major environmental contributor to N 2 O emissions 18,19 . While we attempt to document prior associations, by Cakmak et al 2 and others, between certain air pollution exposures and hospitalization for epilepsy for years 2001 to 2005, we also wish to test our hypothesis that increasing use of anthropogenic nitrogen-based fertilizers in agriculture (the most recognized causal environmental contributor to N 2 O emissions) may be significantly and negatively associated with hospitalization for epilepsy.…”
mentioning
confidence: 99%
“…In areas where highly oxygen-deficient waters extended over the continental shelf, extreme accumulation of N 2 O has been found before in the Arabian Sea (Naqvi et al, 2010(Naqvi et al, ., 2006 and off Chile (Farías et al, 2015) and has been explained by rapid changes in the environmental conditions: Naqvi et al (2000) explained the extreme N 2 O accumulation over the Indian shelf with the response of denitrifying enzymes to transient oxygen depletion. N 2 O thus accumulated when waters reached suboxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the relative contribution to ammonium oxidation, quantified by the ammonia monooxygenase subunit A gene (Molina et al, 2010), and dark carbon assimilation rates (Farías et al, 2009), showed that archaea had a greater potential activity relative to the homologous bacteria in the system. Also, the Thaumarchaeota are mainly associated with the oxycline (Belmar et al, 2017), where N 2 O hotspots are frequently observed (Cornejo and Farías, 2012;Farías et al, 2015), further suggesting their possible participation in N 2 O production in this layer, particularly as the isotopic signature suggests ammonium oxidation by archaea is a major precursor of N 2 O in the ocean (Santoro et al, 2011). To reconcile the inhibitor results with all other evidence, we speculate that GC7, as a growth inhibitor of archaea, might not affect archaeal metabolism in short-term incubations, thus masking the relative importance of this domain for AO during this study.…”
Section: Cycling Of Dissolved Inorganic 15 N Compoundsmentioning
confidence: 99%